Formulation A in the prevention of rheumatoid arthritis: a study protocol for a multicenter randomized controlled trial - Gao, Kaixin; Wen, Yu; Yu, Yihang; Peng, Jianhong; Liang, Weidong; Shen, Zhengdong; Zhang, Lei; Chu, Yongliang; Mei, Liyan; Du, Haifang; Chen, Xiumin; Wang, Maojie; et al. (Frontiers in Medicine, 2025)
BackgroundInterventions to delay or prevent the onset of rheumatoid arthritis (RA) have attracted much attention in recent years. Researchers are now exploring various prevention strategies but no unified consensus was reached. A traditional Chinese medicine (TCM) prescription, Formulation A (FA), may be potential to reduce the risk of RA development.MethodsThis is a multicenter, double-blind, placebo-controlled, randomized clinical trial. We will enroll 72 participants who are positive for anti-cyclic citrullinated peptide (anti-CCP) antibody but without synovitis. Participants will be randomly assigned to either FA or placebo for 52 weeks. All will then undergo 52 weeks of observation. The primary outcome is the time interval between the study entry and RA diagnosis. The secondary outcomes include the proportions of RA diagnosis, anti-CCP antibody, rheumatoid factor (RF), the high-sensitivity C-reactive protein (hs-CRP), the erythrocyte sedimentation rate (ESR), the 28-tender joint count (TJC28), the 28-swollen joint count (SJC28), morning stiffness time, the visual analog scale (VAS), Patient’s Global Assessment (PtGA), Physician’s Global Assessment (PGA), Health Assessment Questionnaire (HAQ), Generic Quality of Life Inventory-74 (GQOLI-74) scores, and ultrasound images of joints.DiscussionThis study attempts to test the feasibility of a clinical trial using FA in RA prevention. It will lay the foundation for future research and ensure validity.